Real Workload-Situated Training in COVID-19 Prevention of General Practice Residents in China: A Situated Cognition Study - Xin, Rao; Li, Luo; Qiaoli, Su; Xingyue, Wang (Frontiers in Public Health, 2021)
Object : Residents' participation in epidemic prevention and control is not only a field workload participation in public health disease prevention and control, but also a rare and value-oriented training experience.This study aims to explores the research on the training content, ability improvement and cognitive load of the resident at different time points (before, in and after the outbreak of the epidemic) in a real situation, to used in the study of the resident training process , and to demonstrate past and future training effects of epidemic prevention and control. Methods: Situated cognition study is designed, including situation context design, legitimate peripheral participation, and construction of a community of practice. Object cognitive load scale (NASA-TLX scale) and self-developed questionnaires were adopted to conduct a questionnaire survey on resident doctors . SPSS 23.0 statistical software for statistical analysis of data. Result: NASA scale shows: mental and cognitive stress (62.41%), physical and physical burden (60.99%), and time urgency (61.7%) , The degree of effort required (65.25%), task pressure, stress or worry (62.41%), the indicators of cognitive load showing "relatively large" statistics are: mental and cognitive stress (12.06%), physical And physical burden (20.57%), time urgency (21.99%), degree of effort required (21.99%), task pressure, stress or worry (11.35%), generally indicating that the intensity of on-site epidemic prevention and control (training) can be tolerated . In particular, there was no statistical difference in the cognitive load intensity of training before and after the epidemic occurred at different lengths of time (P<0.05).Before the outbreak of the epidemic, the public health knowledge and training received came from undergraduate education (83.16%), training stage (69.47%), online self-study (49.16%) and continuing education (20.53%). Conclusion: Former medical school education and training at the regulatory training stage have a good effect for residents to master the ability of epidemic prevention and control, and to prepare for the needs of epidemic prevention and control physically and mentally. After this stage, the epidemic prevention and control training under the real situation will make a great contribution to the self-assessment and performance improvement of the final general practitioners.